Osmotic Dehydration of Nectarines: Influence of the Operating Conditions and Determination of the Effective Diffusion Coefficients - Rodriguez, Maria Marcela (2013)
The aim of the present work is to study the kinetics of osmotic dehydration of Caldesi nectarines (Prunus persica var. nectarina) evaluating the effect of osmotic solution concentration, type of solute, temperature, fruit/solute ratio and process time on moisture content, water loss, soluble solids content and solids gain. The process analysis was carried out experimentally and numerically through the mathematical modelling of mass transfer. Hypertonic solutions of glucose syrup and sorbitol (40 and 60 % w/w) were used for dehydration, during 2 h of process at temperatures of 25 and 40 °C, with fruit/osmotic agent ratio of 1:4 and 1:10. Water loss and solids gain showed significant differences depending on the type and concentration of the osmotic agent, process time and fruit/solution ratio. The concentration interacted significantly with all variables; in addition, there was an interaction between the type of osmotic agent and the relationship between fruit and the osmotic agent. The effective diffusion coefficients were obtained from the analytical solution of Fick's second law applied to flat-plate geometry and by solving the mass transfer microscopic balances by finite element method, taking into account the real geometry of the nectarine pieces. The values obtained from Fick's law varied between 1.27 × 10-10 and 1.37 × 10-08 m2 s-1 for water and from 1.14 × 10-10 to 1.08 × 10-08 m2 s-1 for soluble solids, while the values calculated by finite elements method ranges were between 0.70 × 10-09 and 4.80 × 10-09 m2 s-1 for water and between 0.26 × 10-09 and 1.70 × 10-09 m2 s-1 for soluble solids. The diffusion coefficients values obtained from the numerical solution are consistent with those published in literature.